Evektivitas Biochar Sekam Padi dan Pupuk Fosfat pada Lahan Marginal Terhadap Pertumbuhan Vegetatif dan Hasil Polong Edamame (Glycine max (L) Merr.) - Wahyuni Putri Armita; Made Deviani Duaja; Ahmad Riduan (Jurnal Media Pertanian, 2026)
The aim of this study was to evaluate the effectiveness of different doses of rice husk biochar and phosphate fertilizer on the vegetative growth of edamame grown on marginal soil. The experiment was arranged in a randomized complete block design (RCBD) with a factorial pattern consisting of two factors and three replications. The first factor was the application of biochar with four levels: b0 (control, without biochar), b1 (10 t ha ha-¹ rice husk biochar), b2 (20 t ha-¹ rice husk biochar), and b3 (30 t ha ha-¹ rice husk biochar). The second factor was the dosage of phosphate fertilizer with three levels: p1 (0 kg ha-¹ TSP), p2 (75 kg ha-¹ TSP), and p3 (150 kg ha-¹ TSP). The observed parameters included plant height, leaf area index, number of branches, leaf chlorophyll content, flowering time, and edamame pod yield. The results of soil analysis indicated that the Ultisol used in this study had acidic pH, high phosphorus content, moderate nitrogen and potassium levels, and low organic carbon. The results showed no significant interaction effect on plant height, leaf area index, and flowering time. However, a significant interaction was observed on the number of branches, leaf chlorophyll content, and edamame pod weight.